Comparison of architect assay and elecsys HBs Ag II assay in the quantification of hepatitis B surface antigen in chronic HBV patients - T. Uma Arasu; P. Kanchanadevi; A. Shajahan; Thirunavukkarasu Dharmalingam; Arbind Kumar Choudhary (Romanian Journal of Infectious Diseases, 2023)
Background. Hepatitis B virus (HBV) infection is a global health concern, with an estimated 296 million chronic carriers worldwide. Quantification of hepatitis B surface antigen (HBsAg) is a crucial tool in HBV disease management, providing valuable insights into disease progression and treatment efficacy. Objective. To evaluate the comparative performance of the Abbott Architect HBsAg QT and Roche Elecsys HBsAg II assays in quantifying hepatitis B surface antigen (HBsAg) levels in patients with chronic hepatitis B (CHB). Methods. This prospective study enrolled 60 confirmed CHB patients between February 2021 and November 2021. HBsAg levels were measured using both assays and subsequently log-transformed (log10 IU/mL) for statistical analysis. Interclass correlation coefficient (ICC), Pearson correlation coefficient, and Bland-Altman analyses were employed to assess assay concordance and systematic bias. Results. A statistically significant positive correlation was observed between the Elecsys HBsAg II and Architect HBsAg QT assays for both untreated and treatment-receiving CHB patients (ICC values not specified, p <0.001). Notably, Architect consistently yielded higher HBsAg measurements compared to Elecsys. Conclusion. Both the Elecsys HBsAg II and Architect HBsAg QT assays demonstrate robust correlation in quantifying HBsAg levels in CHB patients. However, the Architect assay exhibits a systematic positive bias relative to Elecsys, which should be considered when interpreting results and making clinical decisions. Both tools provide reliable assessments for HBsAg quantification within CHB management strategies, but it is essential to be aware of potential assay-specific differences.